Characterizations for the fractional maximal commutator operator in generalized Morrey spaces on Carnot group. Issue 6 (3rd June 2019) - Guliyev, Vagif; Ekincioglu, Ismail; Kaya, Esra; Safarov, Zaman
ABSTRACT: In this paper, we will obtain the new results of the strong and weak Spanne-Guliyev, Adams-Guliyev and Adams-Gunawan type boundedness characterization of the fractional maximal operatorM α in generalized Morrey spaces, respectively. Moreover, we will give a characterization for the boundedness of the fractional maximal commutator operatorM b, α in generalized Morrey spaces.